Risk Factors of Febrile Urinary Tract Infection after Ureteral Reimplantation in Infant - Seungsoo Lee; Jae Min Chung; Sang Don Lee (Urogenital Tract Infection)
Purpose Children with febrile urinary tract infection (fUTI) and vesicoureteral reflux (VUR) show significant morbidity. Few studies have examined the incidence of fUTI after ureteral reimplantation for congenital urinary tract anomalies, particularly in infants. Therefore, this study examined the incidence and risk factors of fUTI after ureteral reimplantation in infants. Materials and Methods Children under one year of age, who underwent ureteral reimplantation from July 2017 to December 2018, were reviewed retrospectively. The patients’ data were analyzed to evaluate the predictors of fUTI after ureteral reimplantation. Results Ureteral reimplantation was performed in 16 patients (25 ureters) at a mean of 8.9±2.8 months. The preoperative diagnosis was VUR 14 (87.5%), obstructive megaureter 1 (6.3%), duplicated ureter 1 (6.3%). Postoperative fUTI occurred in five patients (31.3%) during the follow-up period (average 9.6±5.9 months, range 3-18 months). UTI occurred at 40.8±16.6 (17-61) days after surgery. Fourteen ureters were implanted with a ureteral catheter for three days, and 11 ureters were implanted with a double J ureteral stent for six weeks. The children’s age, sex, surgical method, renal scar, reflux grade, laterality, persisting VUR, and presence of double J ureteral stent were not predictive factors for postoperative fUTI. Conclusions The incidence of fUTI after ureteral reimplantation in infants was 31.3%, and all fUTI occurred within two months after surgery. The risk factors associated with fUTI after ureteral reimplantation could not be predicted.